Penerapan model pembelajaran Problem Based Learning untuk meningkatkan kemampuan memahami materi peralatan ringan dan berat pekerjaan konstruksi siswa kelas XI DPIB SMK Negeri 1 Klego tahun pelajaran 2021/2022 - Untung Heksancoko (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The lack of application of student-centred learning causes students to lack understanding of the material they are studying. The impact is the low understanding of students' abilities. Therefore, this classroom action research aims to apply a student-based learning approach using a problem-based learning model to improve students' understanding skills. The method used the Kemmis & Taggart Model Classroom Action Research that every cycle in the research consists of four stages. It is planning, action, observing, and reflecting. This research is carried out in 2 cycles, each containing 2 lessons. The data was from the results of students' cognitive test questions. Based on the results of classroom action research carried out in 2 cycles, it can be concluded that the application of the problem-based learning model can improve the ability to understand the material for Heavy and Light Equipment in Construction Work for class XI students of SMK Negeri 1 Klego. It is proven by the increase in student learning outcomes each cycle. In the first cycle, there was an increase in the percentage of completeness from 40% (pre-cycle) to 66% with an average of 75.4 (sufficient category) after only 69 previously. Then in the second cycle, there was an increase in student completeness to 83% with an average score is 81.7 (good category).